The Influence of Information Technology Sophistication, Skills, and Work Experience on the Effectiveness of Accounting Information Systems (An Empirical Study on Savings and Loan Cooperatives in Denpasar City) - Ketut Nadia Anjani Putri; I Ketut Yadnyana (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
In the digital era, savings and loan cooperatives are required to manage their finances efficiently and accountably through the implementation of effective accounting information systems (AIS). AIS plays a crucial role in producing accurate, timely, and reliable financial reports. However, many cooperatives in Denpasar City continue to face challenges such as delayed reporting and low-quality financial information, despite having adopted information technology. This study aims to examine the influence of information technology sophistication, skills, and work experience on the effectiveness of accounting information systems. The sample consists of 98 cooperative employees who use accounting information systems in their work, selected using purposive sampling. Data were collected through questionnaires, and the analysis was conducted using multiple linear regression. The results of the study indicate that information technology sophistication, skills, and work experience have a significant positive effect on the effectiveness of accounting information systems. This research provides empirical evidence supporting the Technology Acceptance Model (TAM), which emphasizes two main factors influencing technology adoption: perceived ease of use and perceived usefulness. The findings are expected to contribute to cooperative management development and encourage improvements in human resource capacity and the use of technology to support better financial governance.